2002
DOI: 10.1592/phco.22.11.898.33628
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Controlled‐Release Oxycodone: A Systematic Literature Review

Abstract: Prescriptions for controlled-release oxycodone, a narcotic analgesic, recently contributed to a dramatic increase in pharmacy costs for a large private insurance company. To determine whether this agent offered clinical benefits over other available drugs that would justify its significantly greater cost, a systematic review of 16 clinical trials was undertaken. The review suggested that immediate-release and controlled-release preparations of oxycodone have similar efficacy and comparable side effect profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…methadone and long-acting morphine) were preferred over proprietary products of equal or lesser efficacy [55]. …”
Section: Methodsmentioning
confidence: 99%
“…methadone and long-acting morphine) were preferred over proprietary products of equal or lesser efficacy [55]. …”
Section: Methodsmentioning
confidence: 99%
“…28 It was approved in 1995 by the Food and Drug Administration (FDA) for use as an analgesic in individuals with moderate to severe pain requiring relief for several days or more. It was judged at the time of its approval to carry a risk of drug abuse because of its properties as a narcotic, and it was placed in Schedule II of the Controlled Substances Act.…”
mentioning
confidence: 99%
“…Several studies in patients after noncardiac surgery reported good pain control and high patient satisfaction with rapid conversion of iv opioid analgesics to oral immediaterelease or controlled-release oxycodone. [4][5][6] A review of the recent literature 7 suggests that immediate-release and controlled-release oxycodone have similar efficacy in the treatment of noncancer pain and similar side effects. Controlled-release oxycodone may offer the advantage of less frequent dosing, thereby decreasing nursing workload.…”
Section: Conclusion : L'oxycodone Peroral Est Efficace Pour Un Contrômentioning
confidence: 99%